Integration of Artificial Intelligence in Online Learning: Analyzing the Impact on Student Learning Outcomes - Qushwa, Febriyanti Ghayatul (International Journal of Instructional Technology, 2023)
This research focuses on analyzing the impact of integrating Artificial Intelligence (AI) in online learning on student learning outcomes. The primary goal of this study is to identify how AI affects learning personalization, student engagement, and feedback provision, as well as its implications for learning effectiveness. This research employs a qualitative method with a phenomenological approach, where data is collected through in-depth interviews and participatory observation at Universitas Nurul Jadid. The findings indicate that AI has a significant positive impact on enhancing learning personalization, improving student understanding, and increasing engagement and motivation. Additionally, AI has proven capable of providing faster and more accurate feedback, which helps students correct their mistakes more effectively. The implications of this research show that AI has great potential to enhance online learning effectiveness but also emphasizes the need for a balance between technology use and human interaction in education. The study also identifies the need for more comprehensive future research to include variations in gender, age, and other learning methods.